Perioperative Complications of Pedicle Subtraction Osteotomy. (November 2016) - Daubs, Michael D.; Brodke, Darrel S.; Annis, Prokopis; Lawrence, Brandon D.
Study Design: Retrospective case series. Objective: To describe the perioperative complications (0 to 90 days) associated with pedicle subtraction osteotomies (PSOs) performed at a tertiary spine center by two experienced spine surgeons who recently adopted the technique. Methods: We reviewed all 65 patients (47 women and 18 men; mean age 60 years, range 24 to 80) who underwent a PSO at our institution. Descriptive data and analysis of complications were limited to the perioperative time (within 90 days of surgery). Data analyzed included operative time, length of stay (LOS), estimated blood loss (EBL), blood products, comorbidities, neurologic complications, and medical complications. Complications were rated as major and minor. Radiographic data was also analyzed. Results: Ten patients (15.4%) had a major complication, and 15 (23%) had a minor complication. There were three perioperative deaths. The most common major complication was neurologic deficit (6.2%, 4/65), three with a permanent foot drop, and one with paraplegia secondary to postoperative hematoma. There were no differences between patients with and without a major complication in regard to age, gender, comorbidities, operative time, number of levels fused, and EBL ( p > 0.05). Patients with a major complication had a longer intensive care unit stay ( p = 0.04). There was no difference in the rate of major complications between the initial and later cases performed. Conclusion: The major complication rate for pedicle subtraction osteotomy was 15% and the minor complication rate was 23%. The most common major complication was neurologic deficit in 6.2%. The complication rate did not change with increased surgeon experience.